Emerging Fungus, Candida auris: A Case Report - Jha, Roshan Kumar; Raut, Shristi; Adhikari, Mahesh; Rai, Junu Richhinbung; Shah, Chhaya; Kattel, Hari Prasad; Sharma, Sangita (Journal of Institute of Medicine Nepal, 2025)
Candida auris is a growing fungal threat that has sparked global concern. It has been linked to healthcare-related outbreaks and infections around the world and has been reported in numerous countries. This case report describes an infection caused by Candida auris in a 21-year-old patient with a prolonged hospital stay. On the 60th day of admission, the patient developed persistent fever and cerebrospinal fluid culture revealed Candida spp. Identification of the species and antimicrobial susceptibility testing was done by VITEK-2. The isolate was sensitive to flucytosine and voriconazole and resistant to fluconazole and amphotericin B. Voriconazole was started after the culture and sensitivity results.